House Ownership Circumstances in Rural Area: Evidence from Indonesia - Thomas Soseco; Dwi Wulandari; Sugeng Hadi Utomo; Bagus Shandy Narmaditya (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2018)
Barriers to entry of housing affordability are not only existed in urban but also in rural areas. This condition makes rural households difficult to obtain their own house. However, it is still common for them to ask help from parents, in term of financial support or buy the house for them. The purpose of this paper aimed at understanding the phenomenon of society in the rural area to meet their need for house ownership. This research used the descriptive method, employed 15 participants in the Village of Olak-Alen, District of Selorejo, Regency of Blitar, Indonesia. The results of this research showed that newly formed households find their most significant obstacle to own house is inadequate income. Their low income is majorly caused by lack of financial literacy and insufficient work experience.